2022
DOI: 10.1371/journal.pone.0275114
|View full text |Cite
|
Sign up to set email alerts
|

A semi-supervised learning approach for automated 3D cephalometric landmark identification using computed tomography

Abstract: Identification of 3D cephalometric landmarks that serve as proxy to the shape of human skull is the fundamental step in cephalometric analysis. Since manual landmarking from 3D computed tomography (CT) images is a cumbersome task even for the trained experts, automatic 3D landmark detection system is in a great need. Recently, automatic landmarking of 2D cephalograms using deep learning (DL) has achieved great success, but 3D landmarking for more than 80 landmarks has not yet reached a satisfactory level, beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Six studies used an image dataset of CT, two studies CBCT and four studies used both. One study used as dataset both annotated CBCT images (labeled images) and not-annotated ones (unlabeled) [29] and three studies [30][31][32] used a dataset composed by labeled CT images and a landmark dataset of the 3D positions of landmarks from CT. One study reported the mean error in pixels dimension [33] instead of mm, and for this review, it was converted in mm using the pixel-to-mm conversion rate reported in the article. Studies detected a mean (± standard deviation) of 47(± 35) landmarks, with a 5-105 range.…”
Section: Study Selection and Qualitative Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies used an image dataset of CT, two studies CBCT and four studies used both. One study used as dataset both annotated CBCT images (labeled images) and not-annotated ones (unlabeled) [29] and three studies [30][31][32] used a dataset composed by labeled CT images and a landmark dataset of the 3D positions of landmarks from CT. One study reported the mean error in pixels dimension [33] instead of mm, and for this review, it was converted in mm using the pixel-to-mm conversion rate reported in the article. Studies detected a mean (± standard deviation) of 47(± 35) landmarks, with a 5-105 range.…”
Section: Study Selection and Qualitative Analysismentioning
confidence: 99%
“…For eleven studies the reported outcome was the mean error and the standard deviation between manual and automatic landmarking and they were included in the meta-analysis [29,30,[33][34][35][36][37][38][39][40][41]. Four studies didn't report the standard deviation [31,32,42,43]; thus, they were excluded. Detailed information about studies' characteristics can be found in Table 1.…”
Section: Study Selection and Qualitative Analysismentioning
confidence: 99%
“…The decoder D is trained to generate normal CVS-like output. In other words, operation D • E transforms X to lie in or near the learned manifold using normal CVS data [47,58]. Therefore, the residual r can be viewed as an anomaly score, where r is small if X is normal CVS data, and large if X is motion-influenced CVS data.…”
Section: Manifold-learning Approachmentioning
confidence: 99%
“…where KL is Kullback-Leibler divergence and Σ is a 10 × 10 diagonal matrix whose (i, i) entry is σ i . This term enables VAE to learn dense and smooth latent space embedding in or near N (0, I) [31,50,58].…”
Section: B22 Variational Auto-encoder (Vae)mentioning
confidence: 99%
“…A knowledge-based method [44] was reported in 2015. Various kinds of learning-based methods [45][46][47][48][49][50][51][52][53][54][55] have been reported. In our experience with 2D cephalograms [27][28][29], a multi-phased deep learning system was able to predict coordinate values with high precision.…”
Section: Introductionmentioning
confidence: 99%